2020
DOI: 10.1103/physreva.101.022504
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine transitions in the first overtone mode of hydrogen deuteride

Abstract: Beyond the metrology and computational challenges associated with molecular hydrogen, key data are expected to assess the physics of simple molecular systems, and even the New Physics beyond the Standard Model. To assist the deciphering of Doppler-free spectra obtained at very high accuracy (∼ 10 −9), we report on hyperfine transitions of HD in the lowest vibrational levels of the ground electronic state. Using the spin-rotation, nuclear spin-spin and quadrupolar hyperfine couplings determined by means of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 75 publications
2
8
0
1
Order By: Relevance
“…1. Our analysis of the hyperfine structure of this P(1) line is found to be in excellent agreement with that of other recent analyses [28,29].…”
Section: Hyperfine Structuresupporting
confidence: 92%
“…1. Our analysis of the hyperfine structure of this P(1) line is found to be in excellent agreement with that of other recent analyses [28,29].…”
Section: Hyperfine Structuresupporting
confidence: 92%
“…Band origins T v and rotational constants B v and D v are determined by fitting the energies calculated by the program H2Spectre [1] for the first three rotational levels in each vibrational state. The hyperfine parameters c H,v , c D,v , eQq 0,v , and S v ("c dip ") are taken from Dupré [21]; the signs of c H,v and c D,v have been inverted to correctly reproduce the results from that work. Eigenenergies and eigenvectors based on these parameters are calculated using the program spcat [22].…”
mentioning
confidence: 99%
“…The disagreement between recent measurements of rovibrational dipole transitions in the HD molecule [17][18][19] has been attributed to the underlying hyperfine structure of rovibrational states, which were recently studied by Diouf et al [37]. Theoretical studies of the hyperfine components of rovibrational dipole lines in HD were reported [38][39][40] but no such a study concerning quadrupole transitions in H 2 or D 2 was performed.…”
Section: Introductionmentioning
confidence: 99%